3 CHAMAEZA ANTTHRUSHES IN EASTERN BRAZIL (FORMICARIIDAE) - Willis, E. O. (Cooper Ornithological Soc, 1992)
There are three, not two, sibling antthrushes of the genus Chamaeza (Formicariidae) in eastern Brazil. One is the short-tailed, large, pale-billed, lower montane C. campanisona, with a spotted throat, dark forehead, and a long song ending in several grunts. The second is the long-tailed, small, dark-billed, montane and southern C. ruficauda, with barred undertail coverts and a short upscale song. The third is medium-tailed, small, dark-billed, midmontane, with a long upscale song like that of midmontane so-called ruficauda in Colombia and Venezuela. This northern group is like the third Brazilian species in proportions but not in coloration, so is considered to be the separate species C. turdia. The third Brazilian bird is probably C. meruloides Vigors 1825, based on an 1826 color plate; type specimens were sold at auction and have disappeared. It has a reddish crown and olive-brown back as in C. campanisona but reddish forehead and tail as in C. ruficauda; the throat is unspotted but the rest of the underparts are as in C. campanisona. C. meruloides and C. turdina form a vocally similar superspecies.
Keywords: BRAZILIAN FORESTS; CHAMAEZA; CONSERVATION; FORMICARIIDAE; HOLOTYPES; MUSEUMS